1990
DOI: 10.1161/01.cir.81.3.872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of desmopressin acetate on platelet aggregation, von Willebrand factor, and blood loss after cardiac surgery with extracorporeal circulation.

Abstract: The effects of desmopressin acetate (DDAVP) on platelet aggregation and the von Willebrand factor antigen (vWF: Ag) were studied in 19 patients undergoing cardiac surgery with extracorporeal circulation. The patients represented one of five blocks in a randomized double-blind placebo-controlled parallel group trial on the effects of DDAVP on postoperative bleeding after uncomplicated coronary artery bypass operations. After termination of extracorporeal circulation, DDAVP (0.3 jig/kg body wt) or its vehicle wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Of these 142 trials, 95 were apparently randomized, controlled studies. Nine studies were excluded because no clinical outcome other than blood loss was available, [7][8][9][10][11][12][13][14][15] eight studies were found not to be randomized after more thorough analysis, [16][17][18][19][20][21][22][23] five studies concerned cardiac surgery in child- ren, [24][25][26][27][28] and there was one double report. 29,36 66,75,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In addition, 12 studies compared treatment with the conventional dose of aprotinin with lower doses of aprotinin.…”
Section: Literature Search and Methodological Gradingmentioning
confidence: 99%
“…Of these 142 trials, 95 were apparently randomized, controlled studies. Nine studies were excluded because no clinical outcome other than blood loss was available, [7][8][9][10][11][12][13][14][15] eight studies were found not to be randomized after more thorough analysis, [16][17][18][19][20][21][22][23] five studies concerned cardiac surgery in child- ren, [24][25][26][27][28] and there was one double report. 29,36 66,75,[86][87][88][89][90][91][92][93][94][95][96][97][98][99] In addition, 12 studies compared treatment with the conventional dose of aprotinin with lower doses of aprotinin.…”
Section: Literature Search and Methodological Gradingmentioning
confidence: 99%
“…Currently, to our knowledge, there are no agents directed at improving functionality of platelets with respect to induced platelet aggregation. Although DDAVP has been shown to be effective in patients with acquired platelet function defects, results suggest that it can increase vWF:Ag levels but does not alter platelet aggregation . An area of potential research could include development of agents directed toward inducing platelet aggregation.…”
Section: Future Considerations: Untested Modalitiesmentioning
confidence: 99%
“…Although DDAVP has been shown to be effective in patients with acquired platelet function defects, results suggest that it can increase vWF:Ag levels but does not alter platelet aggregation. 80 An area of potential research could include development of agents directed toward inducing platelet aggregation. Although other mechanisms of GIB have been focused on to greater extent, this represents a potential area of research.…”
Section: Target: Platelet Functionmentioning
confidence: 99%
“…On the other hand, in two subsequent large studies of patients undergoing less complex operations with lesser blood loss, there were no significant differences between desmopressin-and placebo-treated patients in terms of total blood loss or transfusion requirements [27,28]. Other studies, mainly in patients undergoing coronary artery bypass grafting and uncomplicated valve replacement, gave conflicting results [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47].…”
Section: Clinical Trials Of Desmopressin In Open-heart Surgerymentioning
confidence: 99%